SCIENTIFIC AND METHODOLOGICAL BASIS OF IMPROVING THE QUALITY MANAGEMENT SYSTEM IN DESIGN ORGANIZATIONS (Marketing Journal, 2025)
This article identifies a number of differences between the quality assurance system in the design process and a similar system in construction organizations. These differences arise from the specifics of the construction project as a product and the characteristics of the design -search process. Quality planning, taking into account t he characteristics of quality formation in the design -search process, has not been sufficiently effective. We consider it appropriate to propose a concept of quality management in design -search organizations. The essence of the quality management subsystem is to identify deviations from the norms in the design estimate documentation in all units and divisions of the enterprise and to show their impact on the final results of the enterpriseʼs activities.
Keywords: project quality; project -research organizati on; concept of quality management